INTERNALISASI NILAI KEPEDULIAN SOSIAL MELALUI PROGRAM JUM’AT BERKAH DI MI TARBIYATUL ISLAM - Zaidanil G., Achmad; Ainul Yaqin , Firdaus; Purwantoro , Farich (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the process of internalizing social awareness values through the Friday Blessings program at MI Tarbiyatul Islam. The background of this research is based on the urgency of instilling character values, particularly social awareness, from an early age amidst the growing tendency towards individualism among students. Social awareness values are crucial and must be instilled through concrete activities, so that students not only understand them theoretically but also are able to implement them in their daily lives. The research method used was a qualitative approach with a descriptive design. Data collection techniques included observation, interviews, and documentation. Data analysis was conducted through the stages of data reduction, data presentation, and drawing conclusions to gain a systematic and in-depth understanding of program implementation. The results indicate that internalization of social awareness values through the Friday Blessings program is realized through the stages of providing understanding, habituation, and role modeling. The program is implemented through sharing activities, such as charity and assistance to others, involving active student participation. The achieved impact is reflected in increased empathy, caring, and sharing habits in students' daily lives.